The Concept of Wathaniyah Ukhuwah in the Qur'an (Analysis Study of Al-Misbah Tafsir) - Ahmad Soandi Sihombing; Munandar, Munandar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
In an era of increasingly intense globalization, multicultural societies face serious challenges in maintaining social cohesion amid cultural, ethnic, religious, and linguistic differences. While diversity is an asset that enriches social life, this reality also harbors the potential for conflict, especially when triggered by negative stereotypes, prejudices, and misunderstandings between groups. Therefore, a multicultural approach supported by inclusive education and cross-cultural dialogue is crucial for fostering empathy, understanding, and peaceful coexistence within society. Indonesia, with its vast geographical character and highly diverse socio-cultural composition, is a real representation of the challenges and potential of multiculturalism. In this context, a multicultural approach not only serves as a social strategy but also as a principle in shaping public policy oriented toward tolerance and respect for differences. However, historical records show that social cohesion in Indonesia has often been shaken, particularly due to horizontal conflicts reflecting the fragility of the foundations of social integration. This situation calls for comprehensive and sustainable solutions that address the root causes of the problem structurally and culturally. One relevant approach to responding to this complexity is the concept of ukhuwah wathaniyah or national brotherhood. This concept emphasizes the importance of collective responsibility and mutual respect among citizens in order to build national solidarity. This article aims to analyze this concept from the perspective of the Qur'an, focusing on M. Quraish Shihab's interpretation in his tafsir Al-Misbah, particularly regarding Surah Al-Hujurat verse 13. Through this tafsir, Quraish Shihab emphasizes that human diversity is part of sunnatullah, intended for mutual understanding, not discrimination. The measure of a person’s nobility is not determined by social status, ethnicity, or cultural affiliation, but by the quality of their piety and character.